2021
DOI: 10.1038/s41467-021-25301-3
|View full text |Cite|
|
Sign up to set email alerts
|

The role of oxygen-permeable ionomer for polymer electrolyte fuel cells

Abstract: In recent years, considerable research and development efforts are devoted to improving the performance of polymer electrolyte fuel cells. However, the power density and catalytic activities of these energy conversion devices are still far from being satisfactory for large-scale operation. Here we report performance enhancement via incorporation, in the cathode catalyst layers, of a ring-structured backbone matrix into ionomers. Electrochemical characterizations of single cells and microelectrodes reveal that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 56 publications
4
96
0
Order By: Relevance
“…As it is most likely that ReCatalyst PtCo/C features a higher fraction of exterior PtCo on carbon than the references (as discussed earlier), the chance for ionomer-induced poisoning for ReCatalyst catalyst is higher compared to the UM catalysts. [72][73][74][75] This hypothesis is further supported by other prior fundamental studies in the liquid electrolyte by N. Marković et al on single crystal surfaces of Pt. 76,77 The authors have shown that the variations in activity for oxygen reduction with crystal facets arise from the different structural sensitivity on the adsorption of anions in the electrolyte.…”
Section: In-situ Electrochemical Performancesupporting
confidence: 77%
“…As it is most likely that ReCatalyst PtCo/C features a higher fraction of exterior PtCo on carbon than the references (as discussed earlier), the chance for ionomer-induced poisoning for ReCatalyst catalyst is higher compared to the UM catalysts. [72][73][74][75] This hypothesis is further supported by other prior fundamental studies in the liquid electrolyte by N. Marković et al on single crystal surfaces of Pt. 76,77 The authors have shown that the variations in activity for oxygen reduction with crystal facets arise from the different structural sensitivity on the adsorption of anions in the electrolyte.…”
Section: In-situ Electrochemical Performancesupporting
confidence: 77%
“…The oxygen diffusivity of state‐of‐the‐art highly oxygen‐permeable ionomer (HOPI) is ≈3 × 10 −10 m 2 s −1 at 30% RH and ≈5 × 10 −10 m 2 s −1 at 90% RH, both at 80 °C. [ 12 ] As a rough comparison, the oxygen diffusivity of SPEEK (1.4 × 10 −10 m 2 s −1 ) and that of SPSU (0.25 × 10 −10 m 2 s −1 ) was observed to be lower than that of the Nafion reference (6.2 × 10 −10 m 2 s −1 ) at the same conditions (80 °C, 75% RH, and 166 kPa abs ). [ 156 ]…”
Section: Challenges and Perspectives For Next‐generation Measmentioning
confidence: 99%
“…Those materials include increased catalytic active sites and intrinsic activity [5,6] and catalyst layers with mesoporous Pt/C from GM R&D. [7] The optimal electrode ionomer should provide high proton conductivity at high temperatures (>100 °C) and low humidity (<50% relative humidity (RH)), thus high ion exchange capacity (IEC) [8] without poisoning the catalyst [9,10] and finally a high oxygen permeability. [11,12] The gas diffusion layers should also be improved to significantly reduce the gas transport losses. [13] The desired high operating temperatures (>100 °C) are a bottleneck for state-of-the-art PFSA membrane-electrode assemblies (MEAs), while being highly attractive to boost efficiency, increase cooling gradients, and increase CO tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…S7, † and the blue part of the diagram represents the free volume produced by polymer chain stacking. 26 The migration and rotation of the polymer chain segments were severely restricted by the crosslinked network of rigid steric hindrance anthracene groups, resulting in a lower polymer chain packing degree. The free volume of CPPOAN is approximately 30% higher than PPOAN via mathematical statistics, 294 nm 3 and 382 nm 3 for PPOAN@Pt/C and CPPOAN@Pt/C, respectively; this provided convincing evidence of the crosslinked rigid steric hindrance anthracene group-induced formation of the porous morphology.…”
Section: Scheme 1 Schematic Of the Anthracene Group Crosslinking Immo...mentioning
confidence: 99%